Politics Multiculturalism of Minority Religions in Demanding Freedom of Worship - Herman Lawelai; Ansar Suherman; Ferdi Ferdi; Mega Seita (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This study addresses the violation of the rights of minority groups to adhere to beliefs other than the six state religions recognized in Indonesia. The government must identify why minority rights are not being fulfilled, and seek to provide answers so that they become the main learning material for diversity in Indonesia. In particular, the power of the state in controlling the dynamics of a pluralistic society is to maintain the integrity and unity of society in an effort to realize the ideals of Pancasila to create a just and prosperous society. This study uses field studies and qualitative research methodologies, including direct observation and in-depth interviews with community leader Towani Tolotang, to obtain objective information about the reality of the object under study. This research shows that until now the Towani Tolotang community in Sidrap Regency still exists in cultural practices and social interaction with the Sidrap community in general because of their political actions. Furthermore, social belief states that the Towani Tolotang community is part of the Bugis community which has a distinctive culture that must be protected.